EXAMINATION OF CATALASE ENZYME IN SEEDS SOME PLANTS AND SOME CHARACTERS OF IT - AL-Anbari, Assel K.; Abdlwahab, Suad KH. (Diyala Agricultural Sciences Journal, 2011)
The study deals with the inve stigation of CAT enzyme in Phasedus vulgaris, Vicia faba, Trigonella,Nigella saliva Brassia oleracca and Beta vulgaris is seeds. The enzyme activity was evaluated. It was found that Nigella saliva showed the highest enzyme activity (1.66) U/mg. The leaves content of total protein was studied, it showed the highest content (1.422) ml/mg for the Phaseodus vulgaris plant. It was selected as Thormal degree for a high level and the stability of the enzyme with the hydrogynic number which depends on the seeds of the black pills (Nigella satvia). This study showed the coming results and the temperature for the activitation of the enzyme (50C°) and it's reactivity is (0.240) u/ml, so the enzyme showed such an obuious stability for (30 min) in (50C°) /and reached (0.348) u/ml /. According to the hydrogenic number and it's power. Reaction reached (0.318) u/ml at (PH=8). So, the enzyme showed the same stability at the hydrogenic number so, it reached in to(0.601) /u/m/.